IMPLEMENTATION OF GREEN BUILDING CONCEPT IN SUMMARECON MUTIARA HOUSING IN MAKASSAR CITY - Andi Besse Opu; Syamfitriani Asnur (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The green building concept is a strategy to reduce global warming caused by the construction sector. The application of the green building concept is increasingly becoming an important topic in modern housing development to reduce negative impacts on the environment in improving the quality of life of its occupants. Green buildings not only focus on energy efficiency and waste reduction but also pay attention to the health of occupants and harmonious integration with the surrounding environment. The application of the green building concept in Summarecon housing has met the Green Building Council Indonesia (GBCI) standards, but due to the need for occupant space, the homeowner changed the green open area, which resulted in the house no longer meeting GBCI standards. This change was caused by the need for a lot of homeowner space, resulting in excessive electricity use and suboptimal air ventilation. This research method was carried out using a qualitative method, this study aims to determine the application of the post-occupancy green building concept in Summarecon Mutiara housing, Makassar City.